Efectos jurídicos por la violación de los derechos humanos universales y principios constitucionales, derivados de la aplicación de la justicia indígena en el Ecuador provincia de Chimborazo, en el periodo 2011-2012. - Aguilar Chocho, José Alfredo (2012)
Our country, after many years of living in a constitutional system of law and social law, the same as characterized by the legislative implementation, attached to the set by lawmakers in Congress, leaving aside the primary or supreme law such as the constitution and many governments that failed leaving a completely negative balance in the legal, political, social, economic and human rights, taking a new course from October 20, 2008, the date on which introduces the new constitution of the Republic of Ecuador